Efektivitas Pelaksanaan Mediasi Dalam Penyelesaain Sengketa Perdata Di Pengadilan Negeri Batam - Sugito, Sugito (Universitas Internasional Batam, 2019)
Abstract To meet the needs of conducting Mediation that is more powerful and able to increase the success of Mediation in the Court so as to reduce the accumulation of cases in the court.Generally, the type of research used in this study is sociological (empirical) research methods. Based on the theory of legal effectiveness, there are 5 factors that influence the legal factor which are the law itself, law enforcement, facilities or facilities, community factors, and cultural factors. The conclusions of the research results that have been done through interviews and direct observations in the Batam District Court is the implementation of the mediation process in the Batam District Court has not been effective.  Keywords: Effectiveness, Implementing Mediation and Civil Disputes.